ANALISIS SPESIFIKASI JABATAN DALAM PENEMPATAN PEGAWAI PADA DINAS PEKERJAAN UMUM BINA MARGA KABUPATEN MUSI RAWAS - Faizal, Andi (Jurnal Governance dan Administrasi Publik, 2020)
Department of Public Works Bina Marga Musi Rawas found that the educational level of employees is not in accordance with the workload they carry, such as a Bachelor of Engineering, but doing the work permit, a Bachelor of Social as bridge maintenance and seski head with just a high school education level. In addition employees have not completed education and training to increase in the structural hierarchy, whereas education is a prerequisite for higher positions. Type a descriptive qualitative research. Analysis of the data in this model consists of four interacting components, namely data collection, data reduction, data presentation and conclusion and verification. The results showed: Head of Section at the Department of Public Works Highways Musi Rawas not in accordance with the educational background and the head just high school graduates. So the lack of conformity of knowledge with education has, therefore, to carry out the job was only obtained by reading the rules in connection with their duties and functions, so that the knowledge possessed had to adjust to the position held, the head generally in carrying out the office does not have skills appropriate to the position held to carry out the duties and functions so that the implementation of the office just relying on the skills sober, and in particular Section Head yet has the ability to hold office. Section Head and optimize rely solely through team research agreement and it is set in the duties to carry out the job.